Train to Pakistan - Khushwant Singh (Grove Press, 1981)
Train to Pakistan is the story of this isolated village that is plunged into the abyss of religious hate. It is also the story of a Sikh boy and a Muslim girl whose love endured and transcends the ravages of war.